Planeación Tributaria de la Empresa FoodGrain SAS (2025)
Tax planning is an essential activity within the organization, especially for small and medium-sized companies in increasingly demanding tax environments. This research analyzes the tax and financial area of the Company FoodGrain SAS, a company specialized in the import and commercialization of agricultural raw materials. The study aims to propose a tax planning strategy to ensure that FoodGrain SAS complies with its acquired tax and regulatory obligations; thereby improving processes, ensuring regulatory compliance and optimizing its cash flow.